ENVIRONMENTAL IMPACT AND REGULATORY COMPLIANCE: A COMPREHENSIVE APPROACH IN MANAGING INSTITUTIONAL PHARMACEUTICAL WASTE - GUPTA, SWETA; DESAI, SONAL (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Apart from the pharmaceutical industries, pharmaceutical institutes are also producing the various types of waste which is a complex issue and that raises several challenges to environmental sustainability as well as public health. Waste produced by pharmaceutical institutes includes chemicals, reagents, biological waste, papers, office supplies and electronic waste, etc. Key topics include the identification and classification of pharmaceutical waste which have potential harm to the ecosystem. Pharmaceutical waste can reach the environment through excretion and improper disposal methods which leads the water contamination, soil pollution and air emission. Surrounding environment directly affect the living things who suffers from infections and diseases from pharmaceutical waste materials. Regulatory frameworks play an important part in defining waste management protocols and proper waste depositories. Compliance with environmental laws and regulations pertaining to pharmaceutical waste disposal is an essential part of pharmacy management. The cost for regulatory compliance in the form of charges are paid by pharmaceutical institutes to comply various laws, rules and standards set by government agencies for waste management. If any institute are fails to comply with the standards of waste management, they have to pay penalties and fines for their improper handling of guidelines. The paper addresses advancements in waste treatment technologies, exploring innovative approaches like autoclaving, microwaving, plasma pyrolysis, incineration and chemical treatments. Understanding of the proper storage and disposal of garbage to prevent contamination and infection.